(untitled) (Journal of Interdisciplinary Insights, 2024)
This study is committed to promoting the development of physical education teaching in China and enriching the theoretical research results of the integration of physical education teaching objectives. This study comprehensively reviewed the research status and achievements of scholars in various countries in the field of integration of physical education teaching objectives, and proposed qualitative research methods based on grounded theory. This study selected a total of 100 original special reports, policy documents and research documents related to the integration of physical education teaching objectives as the original materials, and used open coding to determine 110 original concepts and 17 original categories, which were integrated into four main categories through spindle coding. The results of selective coding showed that there was no inclusion relationship among the four main categories. According to the four main categories finally confirmed, the integration elements of Chinese physical education teaching objectives are "teaching logic construction", "teaching content structure", "teaching evaluation principle" and "teaching method innovation".